Green tea catechins and broccoli reduce fat-induced mortality in Drosophila melanogaster. - Li, Y.M.; Chan, H.Y.E.; Yao, X.Q.; Huang, Y.; Chen, Z.Y. (Journal of Nutritional Biochemistry, 2008)
Dietary fat accelerates the ageing process and causes a greater mortality by accumulating lipid hydroperoxide (LPO) in Drosophila melanogaster. The present study found that the life span of D. melanogaster was shortened from 54 to 6 days in a dose-dependent manner when fat in diet increased from 0% to 25%. The results showed that supplementation of both green tea catechins (GTC) and broccoli extract (BE) reversed partially the fat-induced mortality. The maximum life span was 44 days for the control group fed with a 5% fat, whereas it increased to 50 and 59 days in the GTC- and BE-supplemented groups, respectively. The 50% survival time for the control flies fed with a 5% fat diet was 30 days. In contrast, it increased to 32 and 48 days when GTC and BE were supplemented in the diet. This was consistent with a significant reduction in total body LPO level in D. melanogaster maintained on the GTC- and BE-supplemented diet. Accordingly, catalase and superoxide dismutase (SOD) activities increased significantly in the flies fed with a GTC or a BE diet compared with those fed with a control 5% fat diet. Reverse transcriptase-polymerase chain reaction analysis indicated that the increase in enzymatic activities of catalase and SOD was accompanied by up-regulation of genes for catalase, copper-zinc containing SOD and manganese-containing SOD. It was concluded that GTC and BE reversed the fat-induced mortality in D. melanogaster, most likely but necessarily solely, by up-regulation of endogenous antioxidant enzymes.